Catastrophic Consequences of an Extramarital Affair: A Case Report on Dyadic Death as Filicide- Suicide (Journal of Forensic Medicine & Toxicology, 2026)
Background: Murder-suicide, also known as homicide-suicide or dyadic death, refers to a scenario in which a murder  is committed and the offender commits suicide shortly after the murder. Homicide-suicides are relatively uncommon  and vary by region. Dyadic deaths, including homicide-suicide incidents, are a terrible combination of self-destruction  and interpersonal violence. Filicide–suicide is a subset of dyadic death that occurs when a parent kills their child before  taking their own life. Complex psychosocial factors, such as interpersonal conflict, infidelity, financial constraints, and  emotional instability, are frequently the motivating factors behind these situations. Case Report: We report a case of a middle-aged married man involved in an extramarital relationship who killed his  live-in partner and their toddler son before taking his own life. The woman was found dead, with evidence of ligature  strangulation and blunt force trauma to the head. The son was found nearby with signs consistent with throttling. The  perpetrator husband was found hanging from the ceiling fan at the crime scene. Conclusion: This case highlights the complex relationships between environmental, relational, and psychological pres sures that can result in dyadic death, especially when emotional breakdown, adultery, and marital discord occur. It  emphasizes the importance of early detection of domestic violence, family turmoil, and other risk factors to avert such  disastrous consequences. Meticulous post – mortem examination aids in the medicolegal comprehension of the dynam ics of filicide-suicide and the distinctive patterns of injuries seen in such tragic incidents.
Keywords: (Dyadic death) (filicide–suicide) (strangulation) (throttling) (hanging) (homicide–suicide)